Solvent extraction fractionation of manganese, cobalt, nickel and lithium using ionic liquids and deep eutectic solvents. (1st September 2020) - Zante, Guillaume; Braun, Arthur; Masmoudi, Abderrazak; Barillon, Rémi; Trébouet, Dominique; Boltoeva, Maria
Graphical abstract: Highlights: Solvent extraction of Mn, Co, Ni and Li from sulfuric acid media. Extraction of Mn by TODGA diluted in an ionic liquid. Extraction of Co with [P66614 ][Cl] from highly concentrated sulfuric acid solutions. Extraction of Ni using DES based on lidocaine and carboxylic acids. Hydrometallurgical scheme is proposed for successive separation of valuable metals. Abstract: The recycling of spent lithium-ion batteries remains a challenging task due to the complexity of the leach liquors, which contains several metals in acidic solution. The recovery of valuable metals, viz. Co, Li, Mn, Ni, is also difficult due to the similar chemical behavior of the divalent metal ions. Solvent extraction is mainly used for the separation of these metals, but the conventional extractants used in combination with molecular diluents usually lack of selectivity. We report a new solvent extraction system based on N, N, N', N'-Tetra-n-octyldiglycolamide (TODGA) diluted in the room temperature hydrophobic ionic liquid 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide. Up to 99% of manganese can be extracted in one step with separation factors in the range 40–60 for Mn/Co separation and higher than 200 for the other metals. The mechanism of extraction was detailed. Cobalt separation was done using the ionic liquid tri-hexyltetradecylphosphonium chloride. More than 90% of cobalt can be extracted with very high separation factors. Nickel and lithium separation was carried out by deep eutectic solvents (DESs) based on lidocaine and carboxylic acids. The use of a DES made of decanoic acid and lidocaine shows a high extraction efficiency for nickel while lithium is left in solution.